High-sulfonation-degree long-side-chain PPO / Nafion composite membrane

Through the high-sulfonation long side chain PPO/Nafion composite film, combined with the sulfonated long side chain polyphenylene ether, Nafion and lignin, the problem of insufficient ion conductivity and mechanical strength of existing film materials in high-performance batteries is solved. , achieving higher ion conductivity and chemical stability, improving the overall performance and durability of the battery.

CN119144114APending Publication Date: 2024-12-17山西国润储能科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411250951.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing ion exchange membranes face problems such as limited ion conductivity, insufficient mechanical strength and sensitivity to extreme chemical and thermal environments in high-performance battery applications, and modification or composite technologies often lead to complex and cost-effective preparation processes and may sacrifice. Chemical stability of the material.

Method used

Using a high sulfonation long side chain PPO/Nafion composite membrane, the ion conduction, mechanical strength and chemical stability are optimized through specific components by introducing sulfonated long side chain polyphenylene ether, Nafion and lignin into the membrane. The proportion and preparation method form an efficient ion exchange membrane.

Benefits of technology

It significantly improves the ion conductivity and mechanical strength of the membrane, enhances chemical stability, ensures stable operation under a wide range of environmental conditions, reduces manufacturing costs, and improves the overall performance and durability of vanadium ion flow batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005032234380000131
    Figure BDA0005032234380000131
  • Figure BDA0005032234380000132
    Figure BDA0005032234380000132
  • Figure BDA0005032234380000141
    Figure BDA0005032234380000141
Patent Text Reader

Abstract

The invention relates to the technical field of high-performance membrane materials, and discloses a high-sulfonation-degree long-side-chain PPO / Nafion composite membrane which comprises the following components in percentage by mass: 30-50% of sulfonated long-side-chain polyphenyl ether, 40-60% of Nafion and 5-15% of lignin. The sulfonation degree of the sulfonated long side chain polyphenyl ether is 10-30%; the molecular weight of the sulfonated long side chain polyphenyl ether ranges from 50000 to 100000; the Nafion is a uniform solution obtained by dissolving perfluorinated sulfonic acid resin in DMF (Dimethyl Formamide). According to the high-sulfonation-degree long-side-chain PPO / Nafion composite membrane, the overall performance of a battery is remarkably improved, a large number of sulfonic acid groups are introduced into the composite membrane through high-sulfonation-degree long-side-chain PPO, the ion exchange capacity of the membrane is remarkably improved, long side chains of polyphenyl ether are subjected to sulfonation treatment, ion conduction sites are increased, and the ion exchange capacity of the membrane is improved. And the structural characteristics of polyphenyl ether are retained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-performance membrane materials, in particular to a high-sulfonation-degree long-side-chain PPO / Nafion composite membrane. Background Art

[0002] In existing ion exchange membrane technology, especially in high-performance battery applications such as vanadium ion flow batteries, commonly used materials face many technical challenges. These challenges mainly stem from the limited ionic conductivity of membrane materials, insufficient mechanical strength, and sensitivity to extreme chemical and thermal environments. Although traditional membrane materials, such as simple Nafion membranes, provide good chemical stability and certain ionic conductivity, their high cost and performance degradation under extreme working conditions remain a problem. In addition, these materials often lack the necessary mechanical toughness, making them prone to structural fatigue and damage under high loads or long-term cyclic use.

[0003] In addition, although there are various attempts in the market to optimize the performance of these membranes through modification or composite technologies, such as introducing other polymers or additives through physical or chemical methods to improve ion conductivity and structural stability, these methods often complicate the preparation process and increase production costs. These modification strategies sometimes also sacrifice some of the original excellent properties of the material, such as increasing the ion channel while reducing the chemical stability or thermal stability of the membrane.

[0004] Therefore, it is necessary to develop a new type of composite membrane material that can improve ion conductivity while maintaining or enhancing the mechanical strength and chemical and thermal stability of the membrane, and can operate stably under a wider range of environmental conditions while controlling or reducing manufacturing costs. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a high-sulfonation-degree long-side-chain PPO / Nafion composite membrane, which has high ion conductivity, excellent mechanical strength and chemical stability, so as to improve the overall performance and durability of vanadium ion flow batteries.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a high sulfonation degree long side chain PPO / Nafion composite membrane, the composite membrane comprises the following components in mass percentage:

[0007] Sulfonated long side chain polyphenylene ether 30~50%

[0008] Sulfonated long side chain polyphenylene ether (SL-PPO) is a sulfonated polyphenylene ether containing a large number of sulfonic acid groups. These sulfonic acid groups can provide additional ion exchange sites, thereby enhancing the ion exchange capacity of the composite membrane. A high degree of sulfonation means more protons are available for transfer, thereby improving the proton conductivity of the membrane.

[0009] The long side chain structure of polyphenylene ether can increase the flexibility and mechanical strength of the material. This structural characteristic enables the membrane to withstand greater physical stress during battery operation and avoid breakage during the cycle process.

[0010] Nafion 40~60%

[0011] Nafion is a perfluorinated ion exchange resin containing sulfonic acid groups. Due to its unique microphase separation structure, it can form efficient ion transport channels in the membrane. These channels are very suitable for the rapid transport of ions, especially under high humidity conditions.

[0012] Nafion's perfluorinated background gives it extremely high chemical stability and durability, allowing the membrane to resist strong acids, bases and oxidizing environments, which is very important in battery applications.

[0013] Lignin 5~15%

[0014] Lignin is a natural polymer with a complex three-dimensional network structure. Adding lignin to the composite film can enhance the overall structural stability and provide additional mechanical support.

[0015] The natural composition and structural characteristics of lignin give it good chemical resistance, which helps to improve the stability of the composite film in extreme chemical environments.

[0016] The addition of lignin can affect the membrane microstructure, especially in the basic structure formed by Nafion and SL-PPO. This adjustment helps to optimize ion channels and may further improve ion selectivity and conductivity.

[0017] The design of the high-sulfonation long-side chain PPO / Nafion composite membrane fully utilizes the unique properties and synergy of the three materials, and optimizes ion conduction, mechanical strength and chemical stability through the component ratio. This composite membrane is particularly suitable for high-performance battery applications, such as vanadium ion flow batteries, where the performance requirements of the battery membrane are extremely high.

[0018] Preferably, the sulfonation degree of the sulfonated long side chain polyphenylene ether is 10-30%.

[0019] The degree of sulfonation refers to the content of sulfonic acid groups in polyphenylene ether, which directly affects the ion exchange capacity (IEC) of the material. In the range of 10% to 30% sulfonation, SL-PPO can provide sufficient ion exchange sites to ensure good proton conductivity, which is crucial for the electrochemical performance of the battery.

[0020] At a sulfonation degree of 10% to 30%, SL-PPO maintains sufficient polymer chain interactions, which helps maintain the structural stability of the composite membrane. The appropriate degree of sulfonation helps the membrane maintain high strength and ductility when subjected to mechanical stress, especially during repeated charge and discharge of the battery.

[0021] The moderate degree of sulfonation also helps to enhance the chemical stability of the composite membrane, because the integrity of the polymer skeleton is guaranteed. This enables the composite membrane to resist corrosion in extreme chemical environments such as strong acids and strong bases, which is particularly important in vanadium ion flow batteries because battery fluids are often highly corrosive.

[0022] Preferably, the molecular weight of the sulfonated long side chain polyphenylene ether is between 50,000 and 100,000.

[0023] High molecular weight polymers generally have better mechanical strength and toughness. In the molecular weight range of 50,000 to 100,000, the polymer chains of SL-PPO are long enough to form more physical entanglements between molecules, which helps to improve the overall mechanical strength and durability of the film.

[0024] The appropriate molecular weight is conducive to the dissolution of the polymer in the solvent, ensuring the uniformity and fluidity of the solution during the membrane preparation process. SL-PPO with a molecular weight ranging from 50,000 to 100,000 can be effectively dissolved in commonly used organic solvents, facilitating the subsequent membrane casting process.

[0025] The sulfonated groups in SL-PPO are the key to its ion conductivity. The moderate molecular weight ensures that enough sulfonated groups are distributed on the polymer chain, while avoiding the overly complex and distorted ion conduction paths that may be caused by too high molecular weight. Polymers with molecular weights between 50,000 and 100,000 support the formation of effective ion channels, promote the rapid migration of ions, and improve the overall ion conductivity of the battery.

[0026] Appropriate molecular weight helps improve the chemical stability of the polymer. A higher molecular weight can reduce the relative content of chain end groups, thereby reducing the reactivity of the material in extreme chemical environments. In the typical working environment of the battery, including strong acid or strong base conditions, high molecular weight SL-PPO can show better chemical corrosion resistance.

[0027] Preferably, the sulfonated long side chain polyphenylene ether is prepared by the following method:

[0028] 1. Dissolve polyphenylene ether in dichloromethane to make the concentration of polyphenylene ether 10-20%;

[0029] Dichloromethane is a commonly used organic solvent with a low boiling point and good solubility. Selecting a concentration of 10% to 20% can ensure that the solution has sufficient fluidity to facilitate subsequent chemical reaction processing while avoiding inefficient reactions caused by excessive dilution.

[0030] 2. Add 5-15% of the weight of polyphenylene ether sulfur trioxide and pyridine complex, and reflux at 80-120°C for 4-8 hours;

[0031] Sulfur trioxide is a strong sulfonating agent that can effectively introduce sulfonic acid groups on the benzene ring of polyphenylene ether. Pyridine, as an alkaline substance, can neutralize the generated acid, help control the reaction environment, and reduce side reactions. Controlling the reflux temperature and time is the key to ensuring that the sulfonation reaction is thorough and uniform.

[0032] 3. Precipitating and washing the reaction product by using ethanol as a precipitant;

[0033] Ethanol is a polar solvent that can be used to precipitate most of the undissolved high molecular weight substances. This step is used to remove unreacted low molecular weight substances and by-products from the reaction system and purify the obtained sulfonated polyphenylene ether to ensure its consistency and purity of performance.

[0034] 4. Copolymerize with methacrylate monomer at a molar ratio of 1:1 to 2:1 at 120 to 160°C for 4 to 6 hours, and control the grafting rate to 10 to 30%;

[0035] Methacrylate monomers can be copolymerized with sulfonated polyphenylene ether through free radical reaction to form graft copolymers. This step enhances the mechanical properties and chemical stability of polyphenylene ether by introducing polymethacrylate side chains. Controlling the grafting rate between 10% and 30% ensures sufficient modification effect without excessively affecting the inherent properties of the substrate.

[0036] This preparation method finely controls the conditions and proportions of the chemical reaction, aiming to obtain highly sulfonated long-side chain polyphenylene ether with excellent mechanical properties, high ion exchange capacity and good processability.

[0037] Preferably, the Nafion is a uniform solution of perfluorosulfonic acid resin dissolved in DMF.

[0038] Nafion is treated with DMF as a solvent, which is based on its high solubility and good compatibility with perfluorosulfonic acid resin. DMF can effectively dissolve Nafion to form a uniform solution, which is crucial for the subsequent membrane preparation process.

[0039] Preferably, the lignin is sulfonated and the degree of sulfonation is between 10% and 20%.

[0040] Sulfonation of lignin is the process of chemically modifying the benzene ring structure in the lignin molecule by adding a sulfonating agent (such as sulfur trioxide, chlorosulfonic acid, etc.) to introduce sulfonic acid groups. These sulfonic acid groups increase the polarity and solubility of lignin, allowing it to be better dispersed in water.

[0041] By controlling the dosage of the sulfonating agent and the reaction conditions, the sulfonation degree of lignin can be maintained at 10% to 20%. This range ensures that the lignin retains its natural structural characteristics while obtaining the necessary functional modification.

[0042] Sulfonated lignin contains active sulfonic acid groups that can act as ion exchange sites, increasing the total ion exchange capacity of the composite membrane. This is crucial for improving the ionic conductivity of battery membranes.

[0043] Sulfonated lignin has better hydration capacity due to the introduction of polar sulfonic acid groups, which helps to form more effective ion transport channels in the composite membrane, especially in high humidity environments, helping to maintain the ion conductivity of the battery membrane.

[0044] Lignin itself, as a polymer material, can increase the structural integrity of the composite membrane. Sulfonated lignin can be more evenly distributed in the membrane due to its improved solubility and dispersibility, thereby enhancing the overall mechanical strength and chemical stability of the membrane.

[0045] Preferably, the sulfonation treatment of lignin comprises the following steps:

[0046] 1. Select hardwood lignin, add 10-20% of the weight of lignin sulfonating agent, and react at 90-110°C for 3-5 hours;

[0047] Hardwood lignin contains a higher proportion of aromatic structures than softwood lignin, which makes it more suitable for chemical modifications such as sulfonation. The diversity and richness of aromatic structures provide more possibilities and higher efficiency for sulfonation reactions.

[0048] 10% to 20% of the weight of lignin is added as a sulfonating agent, typically chlorosulfonic acid or sulfur trioxide. This ratio is sufficient to ensure sufficient sulfonation in the lignin while avoiding loss of physical properties due to excessive sulfonation.

[0049] The reaction is carried out at a temperature of 90 to 110°C for 3 to 5 hours. This temperature and time range ensures the complete sulfonation reaction while avoiding the destruction of the lignin structure that may be caused by high temperature. Under this condition, the sulfonation of lignin can achieve an ideal sulfonation degree and increase the water solubility and ion exchange capacity of lignin.

[0050] 2.Use ultrasonic treatment for 0.5 to 1 hour to ensure uniform dispersion;

[0051] Ultrasonic treatment for 0.5 to 1 hour is used to ensure uniform dispersion of the sulfonated lignin in water or other media. Ultrasonic waves can produce tiny vibrations and cavitation effects, which help break up any large aggregates and promote uniform dispersion of lignin in the solution.

[0052] Uniform dispersion helps ensure that lignin can be evenly distributed throughout the membrane during the subsequent composite membrane preparation process, which is crucial to the overall performance of the composite membrane. Uniformly dispersed lignin can form a more uniform microstructure in the membrane, which helps improve the mechanical stability and ion transfer efficiency of the membrane.

[0053] The present invention also provides a method for preparing a high-sulfonation-degree long-side-chain PPO / Nafion composite membrane, comprising the following steps:

[0054] 1. Dissolve the sulfonated long side chain polyphenylene ether and Nafion in a mixed solvent of N,N-dimethylformamide and tetrahydrofuran, respectively, with a dissolution concentration of 10-15%, to obtain a sulfonated long side chain polyphenylene ether solution and a Nafion solution;

[0055] The use of a mixed solvent of N,N-dimethylformamide (DMF) and tetrahydrofuran (THF) can effectively dissolve sulfonated long-side-chain polyphenylene ether and Nafion. The mixed use of DMF and THF helps to adjust the polarity of the solvent to adapt it to the dissolution requirements of the two polymers and ensure the uniformity and stability of the solution.

[0056] Maintaining a dissolved concentration of 10% to 15% is beneficial to the uniform distribution of the membrane material during the subsequent membrane casting process, while avoiding the solution being too viscous, which affects fluidity and membrane formation.

[0057] 2. Slowly mix the sulfonated long side chain polyphenylene ether solution and the Nafion solution at 60-80°C for 1-2 hours;

[0058] Slow mixing at 60 to 80 °C can promote the interaction between polymer chains, help form a uniform solution, and reduce the aggregation of polymer molecules.

[0059] 3. Add lignin solution dropwise at a stirring rate of 500-1000 rpm, the concentration of the lignin solution is 10-15%;

[0060] The dropwise addition of the lignin solution at a stirring rate of 500 to 1000 rpm ensured the uniform dispersion of the lignin, which is critical for the uniformity and functionality of the final membrane.

[0061] 4. Pour the mixed solution into a film casting apparatus, control the thickness to 100-200 microns, and let it stand at ambient temperature for 1-2 hours for preliminary solvent evaporation;

[0062] Controlling the film thickness within the range of 100 to 200 microns ensures the mechanical strength and functionality of the film. Allowing the solvent to evaporate gradually at ambient temperature helps form the initial film structure.

[0063] 5. Soak the preliminary membrane in isopropanol for 2 to 4 hours;

[0064] Isopropyl alcohol can remove residual solvents and low molecular weight substances in the membrane, improving the purity and performance of the membrane.

[0065] 6. Remove the membrane from the isopropanol and place it in a fume hood at ambient temperature for 12 to 24 hours;

[0066] Air drying in a fume hood further removes the solvent and solidifies the membrane structure.

[0067] 7. Place the film in an oven at 60-80°C for heat treatment for 1-2 hours;

[0068] Heat treatment at 60 to 80 °C can further solidify the film and enhance its mechanical properties and chemical stability.

[0069] 8. Immerse the membrane in a solution containing 1-3% cross-linking agent and react at 40-60°C for 2-4 hours;

[0070] Using 1% to 3% of a cross-linking agent at 40 to 60°C can enhance the structural stability of the membrane and improve the chemical and thermal resistance of the membrane through a cross-linking reaction.

[0071] 9. Place the cross-linked film in an oven at 100-120°C for heat treatment for 2-4 hours.

[0072] Heat treatment at 100 to 120°C is used to finally cure the film, improving its stability in long-term use.

[0073] Preferably, the method further comprises post-processing, wherein the membrane is surface treated and then cut and shaped to obtain a composite membrane of a desired size and shape.

[0074] Surface treatment aims to improve the surface properties of the membrane, such as increasing its hydrophilicity or lipophilicity, improving the smoothness of the membrane surface, or facilitating further functionalization treatment.

[0075] Surface treatment can include chemical modification, such as coating a layer of specific polymers or adding surfactants, or physical methods such as plasma treatment to change the properties of the membrane surface. These treatments can optimize the membrane's ion transport characteristics and anti-fouling ability, enhancing its performance in batteries.

[0076] Cutting and shaping is the process of cutting the prepared membrane material into the required size and shape to suit specific battery design and assembly requirements.

[0077] The present invention also provides a vanadium ion flow battery, wherein the battery adopts the high-sulfonation-degree long-side-chain PPO / Nafion composite membrane as its ion exchange membrane.

[0078] Highly sulfonated long side chain polyphenylene ether (SL-PPO) increases the ion exchange capacity of the membrane, thereby improving its ion conductivity. This is crucial for the charging and discharging efficiency of the battery, because higher ion conductivity means that the battery can operate at a higher current density, while increasing the battery's charging speed and discharge capacity.

[0079] The presence of Nafion ensures the mechanical strength and chemical stability of the membrane, enabling it to maintain performance without degradation in the harsh working environment of the battery. At the same time, the addition of lignin further enhances the structural stability of the membrane, especially in long-term operation, lignin helps to maintain the integrity and functional activity of the membrane.

[0080] Special preparation processes of the composite membrane, such as heat treatment and cross-linking, optimize its performance at high temperatures, which is particularly important for vanadium ion flow batteries because the battery generates a lot of heat during operation.

[0081] The present invention provides a high-sulfonation-degree long-side-chain PPO / Nafion composite membrane, which has the following beneficial effects:

[0082] 1. The present invention introduces a large number of sulfonic acid groups into the composite membrane through high-sulfonation long side chain PPO, which significantly improves the ion exchange capacity (IEC) of the membrane. This increased ion exchange site promotes the rapid and efficient transmission of ions, thereby improving the overall ion conductivity. This property is crucial to the charge and discharge efficiency and reaction speed of the battery, especially in electrochemical applications that require a fast response.

[0083] 2. The present invention not only increases the ion conduction sites but also retains the structural properties of polyphenylene ether, such as good elasticity and toughness, by sulfonating the long side chains of polyphenylene ether. These structural properties make the composite membrane have higher mechanical stability, and can maintain performance without degradation under high pressure or high stress operating environment, thus ensuring the reliability of the battery in long-term use.

[0084] 3. The present invention provides excellent chemical stability to the composite membrane through the introduction of Nafion, so that the membrane can resist corrosion in extreme chemical environments, such as strong acids or strong bases. The chemical inertness and structural stability of Nafion play a key role in improving the durability and extending the service life of the composite membrane, especially in continuous high-load electrochemical reactions.

[0085] 4. The design of the composite membrane of the present invention allows it to work stably in a wide temperature range, which is mainly due to the high thermal stability of Nafion and the protective effect of lignin. The structure and chemical properties of lignin help absorb and disperse the heat generated during operation, reducing the negative impact of high temperature on the membrane structure and performance.

[0086] 5. The high-sulfonation long-side chain PPO / Nafion composite membrane of the present invention significantly improves the overall performance of the battery. This includes higher energy efficiency, longer cycle life, and excellent performance under a wide range of operating conditions. This makes the composite membrane very suitable for demanding energy storage and conversion applications, such as vanadium ion flow batteries and other types of high-performance battery systems. DETAILED DESCRIPTION

[0087] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0088] Example 1: Preparation of high sulfonation degree long side chain polyphenylene ether (SL-PPO)

[0089] 1. Material preparation:

[0090] Polyphenylene ether (PPO) was selected with a molecular weight of 75,000.

[0091] Solvent: dichloromethane.

[0092] Sulfonating reagent: sulfur trioxide and pyridine complex.

[0093] Comonomer: methacrylate.

[0094] 2. Sulfonation reaction:

[0095] PPO was dissolved in dichloromethane at a concentration of 15%.

[0096] A sulfur trioxide and pyridine complex was added at 10% by weight of the PPO.

[0097] Reflux at 90°C for 6 hours.

[0098] After the reaction is completed, the product is precipitated in ethanol and washed several times until the washing liquid is colorless.

[0099] 3. Introduction of long side chains:

[0100] Sulfonated PPO was copolymerized with methacrylate at a molar ratio of 1:1.5 at 120°C for 4 hours.

[0101] The grafting rate of the final product was controlled at 20%.

[0102] Example 2: Preparation of Nafion solution

[0103] Materials preparation:

[0104] Perfluorosulfonic acid resin (Nafion)

[0105] Solvent: N,N-dimethylformamide (DMF)

[0106] Solution preparation:

[0107] Nafion resin was dissolved in DMF to prepare a uniform solution with a concentration of 10%.

[0108] Stir at room temperature until the Nafion is completely dissolved to form a transparent and uniform solution.

[0109] This Nafion solution was used in the subsequent steps.

[0110] Example 3: Treatment of lignin

[0111] 1. Material preparation:

[0112] Select hardwood lignin.

[0113] Sulfonating agent: sulfonic acid.

[0114] 2. Sulfonation treatment:

[0115] Lignin was added to 15% by weight of sulfonic acid and reacted at 100° C. for 4 hours.

[0116] After the reaction was completed, the product was washed with water until neutral.

[0117] Ultrasonic treatment was used for 45 min to ensure uniform dispersion of lignin.

[0118] Example 4: Preparation of composite membrane

[0119] 1. Solution preparation:

[0120] SL-PPO was dissolved in a mixed solvent of DMF and THF at a concentration of 12%.

[0121] The Nafion homogeneous solution was also dissolved in a mixed solvent of DMF and THF at a concentration of 12%.

[0122] The SL-PPO solution and the Nafion solution were slowly mixed at 70°C for 1.5 hours.

[0123] Under the condition of stirring rate of 800 rpm, lignin solution was added dropwise, the concentration of lignin solution was 12%, and stirring was carried out for 45 minutes.

[0124] 2. Film casting and initial volatilization:

[0125] Pour the mixed solution into a film casting apparatus and control the thickness at 150 microns.

[0126] The mixture was allowed to stand at room temperature for 1.5 hours to allow the solvent to evaporate.

[0127] 3.Solvent exchange and secondary volatilization:

[0128] The preliminary membrane was immersed in isopropanol for 3 hours.

[0129] Remove the membrane from the isopropanol and place it in a fume hood for 18 hours to allow the solvent to evaporate completely.

[0130] 4. Heat treatment and cross-linking:

[0131] The film was placed in an oven at 70°C for heat treatment for 1.5 hours.

[0132] The membrane was immersed in a solution containing 2% cross-linking agent and reacted at 50°C for 3 hours.

[0133] The cross-linked film was placed in an oven at 110°C for heat treatment for 3 hours.

[0134] 5. Surface treatment and shaping:

[0135] The membrane was treated with 1.5% nitric acid solution for 30 minutes to enhance the surface hydrophilicity and proton conductivity.

[0136] Use precision cutting tools to cut and shape the membrane, ensuring smooth edges without burrs.

[0137] Example 5: Membrane performance test

[0138] Objective: To evaluate the performance of high sulfonation long side chain PPO / Nafion / composite membrane

[0139] Materials and equipment:

[0140] Example 4: Highly sulfonated long side chain PPO / Nafion composite membrane sample prepared

[0141] Ion Exchange Capacity (IEC) Measurement Equipment

[0142] Proton conductivity test equipment (electrochemical workstation)

[0143] Tensile and compression mechanical properties tester (universal material testing machine)

[0144] Electrochemical stability test equipment (battery test system)

[0145] Vanadium ion flow battery simulation environment

[0146] Experiment 1: Ion Exchange Capacity (IEC) Test

[0147] Experimental setup:

[0148] Sample preparation: Cut the composite film sample to a size of 1 cm × 1 cm.

[0149] Solution: 1M H2SO4 solution and 1M NaCl solution.

[0150] Equipment: Ion exchange capacity determination equipment (titration equipment).

[0151] Experimental steps:

[0152] 1. Soak the membrane sample in 1M H2SO4 solution for 24 hours to ensure complete protonation.

[0153] 2. Wash the sample repeatedly with deionized water until the pH value of the washing solution is close to neutral.

[0154] 3. Soak the protonated membrane sample in 1 M NaCl solution for 24 hours.

[0155] 4. Use 0.1 mol / L NaOH solution to titrate the H in the NaCl solution. + , calculate the ion exchange capacity (IEC).

[0156] 5. Repeat the experiment three times and take the average value.

[0157] The experimental results are shown in Table 1:

[0158] Table 1 Ion exchange capacity (IEC) test results

[0159] Sample No. Repeat number Ion exchange capacity (meq / g) Example 4 1 2.1 Example 4 2 2.3 Example 4 3 1.9 average value 2.1

[0160] From the test results in Table 1, we can get:

[0161] By analyzing the data in Table 1, it can be seen that the ion exchange capacity of the composite membrane samples shows certain fluctuations in different repeated tests, ranging from 1.9 meq / g to 2.3 meq / g. These fluctuations may come from small differences in sample preparation or testing. The average ion exchange capacity is 2.1 meq / g, which indicates that the composite membrane has a high ion exchange capacity and is suitable for high-efficiency ion transport applications such as vanadium ion flow batteries. This result meets the requirements of vanadium battery ion exchange membranes and shows good ion exchange properties.

[0162] Experiment 2: Proton conductivity test

[0163] Experimental setup:

[0164] Sample preparation: Cut the composite film sample to a size of 1 cm × 1 cm.

[0165] Humidity control: 80℃ and 100% relative humidity environment.

[0166] Equipment: Electrochemical workstation, frequency range 1 Hz to 1 MHz.

[0167] Experimental steps:

[0168] 1. Place the membrane sample in a humidity controlled environment to equilibrate for 24 hours.

[0169] 2. The resistance of the membrane was measured using the electrochemical impedance spectroscopy method.

[0170] 3. Calculate the proton conductivity based on the resistance value, the formula is as follows:

[0171]

[0172] Where σ is the proton conductivity, L is the thickness of the membrane, R is the resistance, and A is the electrode area.

[0173] 4. Repeat the experiment three times and take the average value.

[0174] The experimental results are shown in Table 2:

[0175] Table 2 Proton conductivity test results

[0176]

[0177]

[0178] From the test results in Table 2, we can get:

[0179] The proton conductivity test of the composite membrane samples at 80°C and 100% relative humidity showed that the proton conductivity was between 0.16S / cm and 0.19S / cm. The average proton conductivity was 0.17S / cm, which performed well compared with the existing high-performance proton exchange membranes and could meet the requirements of high-efficiency battery applications. This shows that the composite membrane has sufficient ion conductivity and can work stably in high humidity and high temperature environments such as proton exchange membrane fuel cells.

[0180] Experiment 3: Mechanical properties test

[0181] Experimental setup:

[0182] Sample preparation: Cut the composite film samples into standard tensile test bars (ASTM D638).

[0183] Equipment: Universal materials testing machine with tension and compression grips.

[0184] Experimental steps:

[0185] 1. Fix the film sample in the fixture of the universal material testing machine.

[0186] 2. Set the stretching rate to 10 mm / min.

[0187] 3. Perform a tensile test and record the stress-strain curve.

[0188] 4. Calculate the tensile strength and elongation at break.

[0189] 5. Repeat the experiment three times and take the average value.

[0190] The experimental results are shown in Table 3:

[0191] Table 3 Mechanical properties test results

[0192]

[0193] From the test results in Table 3, we can get:

[0194] Mechanical test results show that the tensile strength of the composite membrane samples is between 33MPa and 36MPa, and the elongation at break is between 145% and 155%. The average tensile strength is 34MPa, and the average elongation at break is 151%. These data indicate that the composite membrane has excellent mechanical strength and flexibility, and can withstand the mechanical stress that may be encountered during the operation of vanadium flow batteries. Such mechanical properties ensure the durability and stability of the composite membrane in long-term operation.

[0195] Experiment 4: Electrochemical stability test

[0196] Experimental setup:

[0197] Sample preparation: Composite film sample, size is 1cm×1cm.

[0198] Battery simulation environment: using vanadium ion solution (1.6M VOSO4+2.0M H2SO4).

[0199] Equipment: Battery test system with voltage range from 0.8V to 1.6V.

[0200] Experimental steps:

[0201] 1. Assemble the membrane samples into single cells.

[0202] 2. Use vanadium ion solution as the electrolyte.

[0203] 3. Perform cycle test in the voltage range of 0.8V to 1.6V.

[0204] 4. The electrochemical stability of the membrane was tested every 100 cycles, and the battery performance (e.g., voltage, energy efficiency) was recorded.

[0205] 5. Record the cycle life of the membrane until significant performance degradation occurs.

[0206] The experimental results are shown in Table 4:

[0207] Table 4 Electrochemical stability test results

[0208]

[0209]

[0210] From the test results in Table 4, we can get:

[0211] The results of the electrochemical stability test showed that the energy efficiency of the composite membrane sample dropped from 86% to 83% after up to 1000 electrochemical cycles, and the starting voltage increased from 1.1V to 1.4V. Although the performance began to decline after 1000 cycles, the composite membrane can still maintain a relatively high energy efficiency and stable voltage output. This shows that the composite membrane has good electrochemical stability and is suitable for battery systems with high cycle stability requirements. After more than 1000 cycles, although the performance has declined, the composite membrane still shows acceptable durability.

[0212] These test results show that the high-sulfonation long-side chain PPO / Nafion composite membrane performs well in ion exchange capacity, proton conductivity, mechanical properties and electrochemical stability. These properties make it an ideal choice for vanadium ion flow batteries and other demanding electrochemical applications. The comprehensive performance of the composite membrane shows that it can provide long-lasting and stable performance in harsh environments and is a new material with practical application prospects.

[0213] Comparative experiment 1:

[0214] Objective: To verify the effects of sulfonated long side chain polyphenylene ether (SL-PPO) with different sulfonation degrees on the ion exchange capacity, proton conductivity and mechanical properties of composite membranes.

[0215] Experimental procedures

[0216] 1. Composite membrane preparation:

[0217] According to the membrane preparation method of Example 4, SL-PPO with different sulfonation degrees (5%, 10%, 20%, 30%, 35%) were added respectively, and the other steps remained unchanged to prepare 5 composite membrane samples, which were cut into a size of 1 cm×1 cm.

[0218] 2. Ion exchange capacity (IEC) test:

[0219] Cut the sample into 1 cm 2 , immersed in 1 M NaCl solution for 24 h.

[0220] The immersed samples were back-titrated with 0.1 M NaOH solution to calculate the ion exchange capacity.

[0221] 3. Proton conductivity test:

[0222] The proton conductivity of the samples was measured at 100% relative humidity and 80°C using the electrochemical impedance spectroscopy method.

[0223] 4. Mechanical properties test:

[0224] The samples were tensile tested using a universal testing machine, and the tensile strength and elongation at break were recorded.

[0225] The experimental results are shown in Table 5:

[0226] Table 5 Changes of ion exchange capacity, proton conductivity and mechanical properties with SL-PPO sulfonation degree

[0227]

[0228]

[0229] From the test results in Table 5, we can get:

[0230] The results of comparative experiment 1 were used to evaluate the effects of sulfonated long side-chain polyphenylene ether (SL-PPO) with different sulfonation degrees on the performance of the composite membrane in terms of ion exchange capacity (IEC), proton conductivity, tensile strength and elongation at break.

[0231] Ion exchange capacity:

[0232] The samples with low sulfonation degree (5%) showed lower IEC values ​​(average 0.85 meq / g), indicating that the degree of sulfonation was not sufficient to provide more ion exchange sites.

[0233] The samples with medium sulfonation degree (10%-30%) gradually showed increasing IEC values, from 1.65 meq / g to 2.35 meq / g. This increasing trend reflects that more sulfonic acid groups participate in the ion exchange process, enhancing the ion exchange capacity of the membrane.

[0234] The IEC value of the sample with a high degree of sulfonation (35%) decreased (average 2.15 meq / g) because the structure was too loose due to excessive sulfonation, which affected the effectiveness of ion exchange.

[0235] Proton conductivity:

[0236] The proton conductivity increases with the increase of sulfonation degree, from 0.065S / cm (5% sulfonation degree) to 0.185S / cm (30% sulfonation degree), showing an increase in the proton conduction path. However, when the sulfonation degree reaches 35%, the proton conductivity decreases slightly (0.165S / cm), which is due to the loose structure leading to a reduction in the effective proton transfer path.

[0237] Mechanical properties:

[0238] The tensile strength and elongation at break are the highest at 5% sulfonation degree, which are 40.5 MPa and 161%, respectively, indicating that a lower sulfonation degree helps maintain the mechanical strength and elasticity of the membrane.

[0239] As the degree of sulfonation increases, the tensile strength and elongation at break decrease gradually, reaching 32.5 MPa and 141% at 30% sulfonation, respectively. At 35% sulfonation, these values ​​further decrease, showing a significant decrease in mechanical properties.

[0240] The results show that within the sulfonation degree range of 10% to 30%, the composite membrane exhibits good comprehensive performance, with significantly improved ion exchange capacity and proton conductivity while maintaining sufficient mechanical properties.

[0241] Comparative experiment 2: Effect of different lignin addition amounts on composite film performance

[0242] Experimental procedures

[0243] 1. Composite membrane preparation:

[0244] According to the film preparation method of Example 4, different amounts of lignin (3%, 5%, 10%, 15%, 20%) were added respectively, and the other steps remained unchanged to prepare 5 composite film samples, which were cut into a size of 1 cm×1 cm.

[0245] 2. Mechanical properties test:

[0246] The samples were tensile tested using a universal testing machine, and the tensile strength and elongation at break were recorded.

[0247] 3. Chemical stability test:

[0248] The membrane samples were immersed in H2SO4 solution with a pH value of 1 and NaOH solution with a pH value of 13, and the structural integrity of the membranes was observed after 24 hours each.

[0249] 4. Vanadium ion selectivity test:

[0250] The vanadium ion solution was used for testing in an electrochemical test device to evaluate the vanadium ion permeability and membrane selectivity.

[0251] The experimental results are shown in Table 6:

[0252] Table 6 Effect of lignin addition on the mechanical properties and vanadium ion selectivity of composite membranes

[0253]

[0254]

[0255] From the test results in Table 6, we can get:

[0256] The data from comparative experiment 2 show the specific effects of different lignin addition amounts on the performance of the composite film.

[0257] Mechanical strength and elongation at break:

[0258] The samples with low lignin addition (3%) showed relatively low tensile strength (average 37.5 MPa) and elongation at break (average 139%). This is because the lignin content is not enough to significantly improve the structural strength and elasticity of the polymer matrix.

[0259] The samples with medium lignin addition (5%-15%) showed higher tensile strength (up to 45MPa) and elongation at break (up to 160%). Within this range, lignin effectively enhanced the structural integrity of the composite film, which is consistent with the natural polymer structure of lignin increasing the overall toughness and stability of the material.

[0260] The tensile strength and elongation at break of samples with high lignin addition (20%) decreased (average 37.5 MPa and 141%), which was due to the reduced flexibility of the film caused by excessive filler content and the interaction between filler particles weakening the overall continuity of the film.

[0261] Chemical stability:

[0262] The chemical stability ratings showed that samples with moderate addition levels (5%-15%) exhibited better stability under extreme pH conditions, with ratings between 4 and 5, reflecting the effectiveness of lignin in protecting the polymer matrix from chemical attack.

[0263] The samples with low (3%) and high (20%) addition levels had lower chemical stability ratings (average 3), indicating that the protective effect of lignin was insufficient under these conditions.

[0264] Vanadium ion selectivity:

[0265] The results of the vanadium ion selectivity test show that with the increase of lignin addition, the vanadium ion selectivity first increases (from 87% to 93%), reaches the optimum in the range of 5%-15%, and then slightly decreases to 84% (20% addition). This is related to the regulatory effect of lignin on the membrane microstructure. The right amount of lignin helps to form more uniform and appropriately sized channels, promoting the selective transmission of vanadium ions, while too much lignin may cause the structure to be too dense or uneven.

[0266] The results show that moderate lignin addition (5%-15%) provides the best overall performance for the composite membrane, achieving an ideal balance of mechanical properties and functionality, which is fully consistent with the goal of the present invention, namely to utilize the unique chemical and structural properties of lignin to optimize the performance of battery membranes.

[0267] Comparative experiment 3: Performance comparison between composite membrane and pure Nafion membrane

[0268] Experimental procedures

[0269] 1. Membrane sample preparation:

[0270] As the composite membrane, the composite membrane prepared in Example 4 was used.

[0271] For the pure Nafion membrane, a commercially available Nafion membrane was used as a control.

[0272] 2. Proton conductivity test:

[0273] The proton conductivity of the two membranes was measured using an electrochemical impedance spectroscopy (EIS) method at 100% relative humidity and 80 °C.

[0274] 3. Mechanical properties test:

[0275] The samples were tensile tested using a universal testing machine, and the tensile strength and elongation at break were recorded.

[0276] 4. Chemical stability test:

[0277] The membrane samples were immersed in H2SO4 solution with a pH value of 1 and NaOH solution with a pH value of 13, and the structural integrity of the membranes was observed after 24 hours each.

[0278] 5. Vanadium ion selectivity test:

[0279] The vanadium ion solution was used to test in an electrochemical test device to evaluate the vanadium ion permeability and membrane selectivity.

[0280] 6.Battery performance test:

[0281] The membrane samples were tested in actual vanadium ion flow batteries, recording energy efficiency and cycling stability.

[0282] The experimental data are shown in Table 7:

[0283] Table 7 Performance comparison between high sulfonation degree long side chain PPO / Nafion composite membrane and pure Nafion membrane

[0284]

[0285] From the data in Table 7, we can get:

[0286] Comparative Experiment 3 is intended to compare the performance differences between the high-sulfonation-degree long-side-chain PPO / Nafion composite membrane (referred to as composite membrane) of the present invention and the traditional commercial pure Nafion membrane.

[0287] Proton conductivity:

[0288] The proton conductivity of the composite membrane averaged 0.147 S / cm, compared with 0.113 S / cm for pure Nafion membrane. This enhancement suggests that the addition of SL-PPO and the modulating effect of lignin may promote more efficient ion channel formation.

[0289] The introduction of SL-PPO and the optimized ratio of lignin in the composite membrane changed the microstructure of the membrane, which may lead to more ordered or continuous ion channels, thereby enhancing the ion transport efficiency.

[0290] Mechanical properties:

[0291] The composite membrane outperformed the pure Nafion membrane in both tensile strength and elongation at break, with the composite membrane having an average tensile strength of 35 MPa, while the pure Nafion membrane had an average tensile strength of 31 MPa. This difference indicates that the composite membrane has higher structural integrity and elasticity.

[0292] The structural properties and chemical stability of lignin may provide additional mechanical support for the composite membrane, while the long side chain structure of SL-PPO increases the flexibility and strength of the membrane.

[0293] Chemical stability:

[0294] The chemical stability rating of the composite membrane in extreme acid and alkaline environments is generally higher than that of pure Nafion membrane, showing better resistance to chemical corrosion.

[0295] The natural chemical resistance of lignin plays a protective role in the composite membrane, reducing the corrosion of acid and alkali on the membrane material, while the structure of the sulfonated long side chain also helps to protect the Nafion chain segment.

[0296] Vanadium ion selectivity and battery performance:

[0297] The vanadium ion selectivity and battery performance of the composite membrane exceeded those of pure Nafion membrane, indicating that the composite membrane has better potential for battery applications.

[0298] By adjusting the preparation method to optimize the distribution of SL-PPO and lignin, the ion screening performance and electrochemical stability of the membrane were improved, making the composite membrane perform better in battery applications.

[0299] The results of this experiment highlight the importance of the composite material preparation method and the optimization of its component ratios. Through the designed preparation process, the composite membrane fully utilizes the unique properties of each component, such as the ion conductivity of SL-PPO and the structural stability of lignin, which together improve the overall performance of the final product.

[0300] This combined effect not only improves the physical and chemical properties of the composite membrane, but also provides it with obvious advantages in demanding battery applications, confirming the effectiveness and potential of combining natural polymer materials and synthetic polymers to prepare ion exchange membranes. This approach shows that through cross-innovation of materials science and chemical engineering, significant improvements in the performance of traditional materials in battery technology can be achieved.

[0301] Comparative experiment 4: Performance test of composite membrane in actual vanadium flow battery

[0302] Experimental steps:

[0303] 1. Membrane preparation:

[0304] Composite membrane: prepared according to the method of Example 4.

[0305] Commercial membranes: purchased directly from suppliers.

[0306] 2. Membrane installation:

[0307] The two membranes were installed separately in a standard vanadium ion flow battery test cell.

[0308] 3.Battery test:

[0309] Initializes the battery cells, including filling the electrolyte and adjusting the battery to operating temperature.

[0310] The cell test parameters were set to ensure that both membranes were run under the same operating conditions.

[0311] 5. Performance testing:

[0312] Energy Efficiency and Power Density: Energy efficiency and power density are measured over multiple cycles using a battery test system, recording data for both initial and ongoing operation.

[0313] Cycle life: Each membrane was subjected to at least 1000 charge and discharge cycles to observe performance degradation.

[0314] Vanadium ion cross-mixing rate: By analyzing the changes in the composition of the electrolyte, the cross-mixing rate of vanadium ions from the positive electrode to the negative electrode is calculated.

[0315] The experimental results are shown in Table 8:

[0316] Table 8 Performance comparison of composite membrane and commercial membrane in vanadium ion flow battery

[0317]

[0318] From the data in Table 8, we can get:

[0319] Performance advantages:

[0320] Energy Efficiency and Power Density: The composite membranes showed significantly better performance than commercial membranes in energy efficiency and power density tests. This advantage is attributed to the high degree of sulfonation of SL-PPO and the structural characteristics of lignin in the composite membranes. These improved components provide more efficient ion transport paths and reduce internal resistance. This optimization ensures that the composite membranes can provide higher performance in high-demand battery applications such as vanadium flow batteries.

[0321] Cyclic stability and vanadium ion cross-mixing rate:

[0322] Cycling stability: The composite membrane showed better performance stability than the commercial membrane in the charge-discharge cycle test for up to 1,000 times. This shows that the composite membrane is more stable in structure and can withstand long-term electrochemical cycles without significant degradation.

[0323] Vanadium ion cross-mixing rate: The vanadium ion cross-mixing rate of the composite membrane is low. This is due to the combined effect of lignin and sulfonated PPO, which effectively reduces the unnecessary migration of vanadium ions in the membrane, thereby improving the overall efficiency and life of the battery.

[0324] Structural and chemical stability:

[0325] Structural integrity: The addition of lignin enhances the mechanical strength and chemical stability of the composite membrane. The natural chemical resistance and structural complexity of lignin provide an additional layer of protection for the membrane, reducing structural damage under extreme chemical conditions. This property makes the composite membrane more durable than commercial membranes when facing highly corrosive environments such as vanadium battery electrolytes.

[0326] Chemical stability: The chemical stability of the composite membrane is better than that of commercial membranes, a property that is critical to maintaining the long-term performance of the battery, especially in continuously operating vanadium flow battery systems.

[0327] The application of the composite membrane of the present invention in vanadium ion flow batteries shows its significant advantages over conventional commercial membranes. Through the designed material composition and preparation process, this composite membrane not only provides higher energy efficiency and power density, but also ensures a lower vanadium ion cross-mixing rate and stronger cycle stability. These performance improvements are directly attributed to the synergistic effect of sulfonated long side chain PPO and lignin, whose structural characteristics and chemical stability provide substantial improvements in battery operation. Therefore, this composite membrane provides an effective material solution for improving the performance and economic benefits of vanadium flow batteries, and is expected to be promoted and applied in the high-efficiency battery market.

[0328] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high sulfonation degree long side chain PPO / Nafion composite membrane, characterized in that: The composite film comprises the following components in percentage by mass: Sulfonated long side chain polyphenylene ether 30-50%, Nafion 40-60% and lignin 5-15%.

2. The high-sulfonation-degree long-side-chain PPO / Nafion composite membrane according to claim 1, characterized in that: The sulfonation degree of the sulfonated long side chain polyphenylene ether is 10-30%.

3. The high-sulfonation-degree long-side-chain PPO / Nafion composite membrane according to claim 1, characterized in that: The molecular weight of the sulfonated long side chain polyphenylene ether is between 50,000 and 100,000.

4. The high-sulfonation-degree long-side-chain PPO / Nafion composite membrane according to claim 1, characterized in that: The sulfonated long side chain polyphenylene ether is prepared by the following method: Dissolve polyphenylene ether in dichloromethane to make the concentration of polyphenylene ether 10-20%; Add 5-15% of the weight of polyphenylene ether sulfur trioxide and pyridine complex, reflux at 80-120° C. for 4-8 hours; precipitating and washing the reaction product by using ethanol as a precipitant; At 120-160° C., copolymerize with methacrylate monomer at a molar ratio of 1:1-2:1 for 4-6 hours, and control the grafting rate at 10-30%.

5. The high-sulfonation-degree long-side-chain PPO / Nafion composite membrane according to claim 1, characterized in that: The Nafion is a uniform solution of perfluorosulfonic acid resin dissolved in DMF.

6. The high-sulfonation-degree long-side-chain PPO / Nafion composite membrane according to claim 1, characterized in that: The lignin is sulfonated, and the sulfonation degree is between 10% and 20%.

7. The high-sulfonation-degree long-side-chain PPO / Nafion composite membrane according to claim 6, characterized in that: The sulfonation treatment of the lignin comprises the following steps: Select hardwood lignin, add 10-20% of the weight of lignin sulfonating agent, and react at 90-110°C for 3-5 hours; Ultrasonic treatment was used for 0.5 to 1 hour to ensure uniform dispersion.

8. A method for preparing a high-sulfonation-degree long-side-chain PPO / Nafion composite membrane, for preparing a high-sulfonation-degree long-side-chain PPO / Nafion composite membrane as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Dissolving the sulfonated long side chain polyphenylene ether and Nafion in a mixed solvent of N,N-dimethylformamide and tetrahydrofuran at a concentration of 10-15% to obtain a sulfonated long side chain polyphenylene ether solution and a Nafion solution; Slowly mix the sulfonated long side chain polyphenylene ether solution and the Nafion solution at 60-80° C. for 1-2 hours; Under the condition of stirring speed of 500-1000 rpm, adding lignin solution dropwise, the concentration of lignin solution is 10-15%; Pour the mixed solution into a film casting apparatus, control the thickness to 100-200 microns, and let it stand at ambient temperature for 1-2 hours for preliminary solvent evaporation; Soak the preliminary membrane in isopropanol for 2 to 4 hours; Remove the membrane from the isopropanol and place it in a fume hood at ambient temperature for 12 to 24 hours; Place the film in an oven at 60-80°C for heat treatment for 1-2 hours; The membrane is immersed in a solution containing 1 to 3% of a cross-linking agent and reacted at 40 to 60°C for 2 to 4 hours; The cross-linked film is placed in an oven at 100-120° C. for heat treatment for 2-4 hours.

9. The method for preparing a high-sulfonation-degree long-side-chain PPO / Nafion composite membrane according to claim 8, characterized in that: The method further comprises post-processing, wherein the film is surface treated and then cut and shaped to obtain a composite film of a desired size and shape.

10. A vanadium ion flow battery, characterized in that: The battery adopts the high-sulfonation-degree long-side-chain PPO / Nafion composite membrane described in any one of claims 1 to 7 as its ion exchange membrane.